High Seropositivity Rate of Neutralizing Antibodies to Astrovirus VA1 in Human Populations - Andrew B. Janowski; Macee C. Owen; Holly Dudley; Tomás López; Rafaela Espinosa; Memory Elvin-Lewis; Alejandro Colichon; Carlos F. Arias; Peter D. Burbelo; David Wang (mSphere, 2021)
Astroviruses are human pathogens with emerging disease associations, including the recent recognition of their capacity to cause meningoencephalitis. Astrovirus VA1 is the most commonly identified astrovirus genotype from cases of human encephalitis, but it is unknown what percentage of the human population has neutralizing antibodies to VA1.